CATALOGACIÓN CRÍTICA DE ALGUNOS VERTEBRADOS FÓSILES CHILENOS. II. LOS MASTODONTES (Ameghiniana, 2013)
The old and new material, of chilean mastodonts are restudied. Although a new formal classification is not yet proposed, a rearrangement in two entities (generic or specific in level) Is tentatively suggested, both show depressed skulls and molars without trefol-like postrites, but the one (a), restreined to northern Chile, has spiral tusks with enamel band; and the other, common in the whole continental Chile, show simply curved tusks and lacks the enamel Bando other differences are present in the postcranial skeleton.